New records of microfungi from Turkey - Kirbag, S (Pakistan Botanical Soc, 2004)
Plasmopara pusilla (de Bary) Schroter, Peronospora ranunculi Gaum, Hormotheca robertiani (Fr.) Hohnel., Melampsora apocyni Tranzchel, Melampsora magnuisiana Wagn. ex. Kleb., Sporonema punctiforme (Fuckel) Hoehnel., Sporonema phacidioides Desm., Septoria euphorbia Kalchbr., were collected for the first time in Turkey. Short descriptions of fungi are given with their collection sites.